SSR-based molecular characterization of Verticillium wilt resistance in Iranian cotton cultivars - Sanaz Shahbazi; Sara Ghaffarian; Mohammad Razinataj; Mohammad Reza Zangi; Rasmieh Hamid; Bahman Panahi (Biochemistry and Biophysics Reports)
Verticillium wilt (VW) is one of the most devastating diseases affecting cotton (Gossypium spp.), causing significant yield losses worldwide. The development of resistant cultivars is a primary strategy for managing this disease; however, conventional breeding approaches often encounter challenges in balancing resistance with high yield potential. This study aimed to assess the genetic diversity of 25 cotton cultivars using simple sequence repeat (SSR) markers and to identify key polymorphic markers associated with VW resistance. A total of 16 SSR markers were utilized, of which five (DPL405, DPL752, DPL866, DPL890, and DPL0022) were polymorphic. The polymorphism information content (PIC) values ranged from 0 to 0.49, with DPL405, DPL866, and DPL890 being the most informative. Principal coordinates analysis (PCoA) demonstrated genetic differentiation between resistant and sensitive cultivars, with the first axis explaining 41.19 % of the total variation. Resistant cultivars such as Leader, Golestan, and Arya clustered distinctly from sensitive varieties, confirming the effectiveness of the selected markers in genetic differentiation. Despite the promising results, key limitations include the relatively low overall marker polymorphism and the limited number of SSRs used, which may constrain broader genomic coverage and resolution. Nonetheless, the findings provide valuable insights for cotton breeding programs and highlight the potential of SSR markers in supporting marker-assisted selection (MAS) for Verticillium wilt resistance.